Calculation of Tolerances of Landings with A Gap by Software - Косимова Замира Медатовна; Uraimov Mukhammaddiyor Bahodir o‘g‘li (Genius Publishing Group, 2022)
This article discusses the reduction of time when calculating the tolerances of landings with a gap. Computer software for calculating landings with a gap can be used in the educational process, in production when calculating the design in design departments, when compiling the technological process of machining parts and assembling structures.
Keywords: landing with a gap; tolerance; software; analysis; upper deviation; lower deviation